Vascularized lymph node transplantation successfully reverses lymphedema and maintains immunity in a rat lymphedema model - Ahmet Hamdi Sakarya; Chi‐Wei Huang; Chin‐Yu Yang; Hui‐Yi Hsiao; Frank Chun‐Shin Chang; Jung‐Ju Huang (Bioengineering & Translational Medicine, 2022)
Abstract Vascularized lymph node transplantation (VLNT) has shown inspiring results for the treatment of lymphedema. Nevertheless, it remains unclear how VLNT restores lymphatic drainage and whether or not immunity recovers after surgery. Hindlimb lymphedema model was created using rats with extensive groin and popliteal lymph node removable following with radiotherapy, and the lymphedema was confirmed using indocyanine green (ICG) lymphangiography and micro‐computer tomography for volume measurement. VLNT was performed 1 month later. Volume measurement, ICG lymphangiography, histology, and immune reaction were done 1 month after surgery. VLNT successfully reduced the volume of the lymphedema hindlimb, restored lymphatic drainage function with proven lymphatic channel, and reduced lymphedema‐related inflammation and fibrosis. It promotes lymphangiogenesis shown from ICG lymphangiography, histology, and enhanced lymphangiogenesis gene expression. Dendritic cell trafficking via the regenerated lymphatic channels was successfully restored, and maintained systemic immune response was proved using dinitrofluorobenzene sensitization and challenge. VLNT effectively reduces lymphedema and promotes lymphatic regeneration in the capillary lymphatic but not the collecting lymphatic vessels. Along with the re‐established lymphatic system was the restoration of immune function locally and systemically. This correlated to clinical experience regarding the reduction of swelling and infection episodes after VLNT in lymphedema patients.